Stress-Related Behaviors in Companion Dogs Exposed to Common Household Noises, and Owners' Interpretations of Their Dogs' Behaviors - Grigg, Emma K.; Chou, Juliann; Parker, Emily; Gatesy-Davis, Anwyn; Clarkson, Sara T.; Hart, Lynette A. (Frontiers in Veterinary Science, 2021)
Sudden, loud noises are one of the most common triggers for fearful behaviors in dogs, and many companion dogs suffer from noise sensitivity. Existing research focuses on dramatic infrequent sounds (e.g., thunderstorms, fireworks). Anecdotally, and based on reports of undesirable behaviors in response to noises in the home, many common household noises may also be causing fear and anxiety in companion dogs. However, these responses have not yet been studied in home environments. We surveyed 386 dog owners about their dogs’ responses to household sounds, and recorded dog behaviors and human reactions from 62 videos and compilations available on an online video sharing platform, featuring dogs reacting to common household noises. Numerous signs of canine fear and anxiety were reported by survey respondents and observed in the videos, in response to both daily, and irregular but ‘normal’, household noises. Responses were significantly stronger to sounds characterized as high frequency intermittent than to sounds characterized as low frequency continuous. Respondents appeared to underestimate their dogs’ fearfulness, and the majority of humans in the videos responded to their dogs’ behaviors with amusement; welfare concerns were rarely expressed. While these videos cannot be used to calculate actual prevalence of these issues, our data support that some owners are underestimating fearfulness in their dogs in response to household noises, and responding inappropriately to dogs’ expressions of fear and anxiety. Better education is required for dog owners to accurately interpret canine body language, to both safeguard dogs’ welfare and minimize development of anxiety-related behavior problems.